2018
DOI: 10.3390/ma11060920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fine Aggregate Morphology by Image Method and Its Effect on Skid-Resistance of Micro-Surfacing

Abstract: Micro-surfacing is a widely used pavement preventive maintenance technology used all over the world, due to its advantages of fast construction, low maintenance cost, good waterproofness, and skid-resistance performance. This study evaluated the fine aggregate morphology and surface texture of micro-surfacing by AIMS (aggregate image measurement system), and explored the effect of aggregate morphology on skid-resistance of single-grade micro-surfacing. Sand patch test and British pendulum test were also used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Xie et al [ 9 ] evaluated the morphological characteristics of fine aggregates by using three methods and they found that different methods have respective applicability and precision, in which digital image processing technique is useful for designing bituminous materials. Xiao et al [ 10 ] studied fine aggregate morphology by using the aggregate image measurement system and discussed the influences of aggregate morphological characteristics on skid-resistance of single-grade micro-surfacing.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [ 9 ] evaluated the morphological characteristics of fine aggregates by using three methods and they found that different methods have respective applicability and precision, in which digital image processing technique is useful for designing bituminous materials. Xiao et al [ 10 ] studied fine aggregate morphology by using the aggregate image measurement system and discussed the influences of aggregate morphological characteristics on skid-resistance of single-grade micro-surfacing.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that TiO 2 is superior to other photocatalytic materials, such as ZnO, SnO 2 , Fe 2 O 3 , CuO, NiO, and CeO 2 , in its ability to remove NO x and SO x by the photo-decomposition principle under UV light irradiation [ 16 , 17 ]. In addition, the enhanced photodegradation performance of a cement-based composite by controlling the content of TiO 2 in the cement-based composite [ 18 ], the impregnation and coating of sodium silicate on LWAs to provide self-healing properties [ 19 ], the improved skid-resistance of LWAs by controlling aggregate morphology through micro-surfacing [ 20 ], the hydrophobicity control of LWAs modified with sewage sludge [ 21 ], and the embedment of phase change materials into LWAs to improve thermal energy storage characteristics and reduce damage mitigation [ 9 , 22 ] have been studied. Although various studies are being conducted to develop artificial LWAs that can increase the strength and durability of aggregates and exhibit various functions, there has been minimal progress in the development of high-quality multi-functional artificial LWAs that can be applied to high-rise and large-scale buildings.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of fine aggregate content was found to jeopardize the resistance of asphalt mixture on low-temperature cracking [51]. Fine aggregates had a more significant impact on skid resistance on the macro-texture level than micro-texture level [52,53]. Li reported that the complex modulus values between asphaltic mastic and mortar were highly correlated and the dissipated energy method could well explain the fatigue performance of asphalt materials at different scales [6].…”
Section: Introductionmentioning
confidence: 99%